Biocaptura de CO2 em mistura de gás natural por microalgas imobilizadas em matriz híbrida de sílica/alginato - Moraes, Júlia da Costa (2022)
Currently, photosynthetic microrganisms, such as microalgae, have been widely studied as an alternative technology for capturing CO2. The strategy of immobilizing microorganisms in solid matrices is shown as an interesting alternative to solve some operational difficulties in the application of microalgae as technology to capture CO2, such as handling cultures and greater tolerance to external factors. The present work aimed to develop different matrices composed of silica/alginate, varying the concentration of silica precursors, namely: sodium silicate and colloidal silica (Ludox 40 HS). The synthesized materials were characterized in terms of their surface area, durability of cell viability, transparency, optical and physical-chemical properties. Additionally, a new methodology was developed to evaluate the capture of CO2 by microalgae using an innovative pressurized system with natural gas mixture. Several optimization tests were carried out, exploring the influence of several variables, such as: pressure, volume occupied in the bioreactor, cell concentration, presence of agitation and pressure. Once the analysis parameters were fixed, the levels of CO2 capture by immobilized microalgae were investigated for 7 days, evaluating the relative concentrations of this gas using gas chromatography. The results of immobilized microalgae showed levels of CO2 removal even higher than those observed when using free microalgae (41.4% and 32.9%, respectively). This work proved the great potential of application of the biomaterial studied for natural gas processing, making even more possible the adoption of this alternative technology for selective capture of CO2 in large industries.